Peningkatan Kemandirian dan Etika Sosial Anak SMK di Panti Asuhan Yatim Piatu Al Ikhwaniyah, Jurang Mangu Barat, Tangerang Selatan - Nabila Fitriyani Dailami; Amelia Rizkina Putri Naomi; Yublina Bura Kaka; Irfan Rizka Akbar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The Student Creativity Program (PKM) aims to identify and improve the independence and social ethics of vocational high school students living at the Al Ikhwaniyah Orphanage in Jurang Mangu Barat, South Tangerang. The program utilizes a structured coaching approach that includes life skills training, fostering personal responsibility, and strengthening social values ​​such as cooperation, empathy, and discipline. Methods include observation, interviews, and active mentoring in daily activities and training programs. Results indicate an improvement in the children's ability to manage themselves, complete tasks independently, and interact more positively with peers and caregivers. Furthermore, behavioral changes have been observed, including an increased sense of responsibility, social sensitivity, and the ability to work in groups. Overall, this program has proven effective in developing the children's independence and social ethics, while also providing recommendations for developing long-term coaching at the orphanage.